Comparative Analysis Of Online And Offline Promotions On Purchasing Decisions At Food And Beverage Companies In Palembang City (Case Study Of Mein Garden Cafe Palembang) - Rahma, Mutiara Ainur; Harahap, Lily Rahmawati; Ermeila, Sri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine whether there are differences in online and offline promotions on purchasing decisions at food and beverage companies in Palembang City (Case Study Mein Garden Cafe Palembang). The research method used is the Paired Sample T-test. The data used in this study are secondary data, namely data obtained from Mein Garden Cafe Palembang. As well as using primary data obtained from questionnaires distributed to 272 respondents of Mein Garden Cafe Palembang consumers.The results showed that there was a significant difference at Mein Garden Cafe Palembang, it is known that the significant value of 0.045 <0.10, which means that there is a significant difference between online promotion and offline promotion.